Beberapa Motivasi Masyarakat Toraja Memotong Ternak Kerbau Pada Acara Adat (Rambu Solo’ dan Rambu Tuka’) - Sitti Nurani Sirajuddin (State Islamic University (UIN) Alauddin, 2013)
ABSTRACT. This study aimed to determine the motivation of the Toraja people cut buffalo on custom events Rambu Solo’ and Rambu Tuka’. The study was conducted in May 2012 until June 2012 in the districts Makale, Tana Toraja Regency. Populasi was all the people who have done cutting buffalo while the sample of 20 people with using the Delphi method. Data analysis was a descriptive statistical frequency distribution. The results showed people's motivation to cut Toraja buffalo on custom events Rambu Solo 'and Rambu Tuka' consists of extrinsic motives, namely: 1. Driven feeling indebted for families who have a party had first brought and cut the buffalo on the traditional parties that have been held (pay down debt), 2. to preserve the culture and increase revenue (the original income) Tana Toraja, 3.Habits / Rituals and intrinsic motives, namely: 1. Deepen Relationships and 2. Adjusted Economic Capabilities. Keywords:Motivation, Cut, Buffalo, Rambu Solo’, Rambu Tuka’.